2013
DOI: 10.4321/s1130-01082013000300001
|View full text |Cite
|
Sign up to set email alerts
|

Rationalizing the use of PPIs: An unresolved matter

Abstract: The abnormally high use of proton-pump inhibitors (PPIs) has been repeatedly denounced for many years (1), and attention has been drawn towards the economic burden it represents (2,3). Multiple scientific publications have reported this problem in many countries. In the present issue of the Journal an observational, prospective study based on a survey to analyze the inappropriate (not recommended by clinical guidelines) indication of chronic PPI use (daily for over one year) in outpatients seen at a specialty … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2013
2013
2016
2016

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 13 publications
0
7
0
Order By: Relevance
“…We have read with interest the paper by Sanchez-Cuén JA et al (1) on inadequate indications in the chronic use of proton pump inhibitors (PPIs), as well as the editorial on rationalizing the use of PPIs by Ponce and Esplugues (2).…”
Section: Abstract: Proton Pump Inhibitors Prescription Clinical Prmentioning
confidence: 99%
“…We have read with interest the paper by Sanchez-Cuén JA et al (1) on inadequate indications in the chronic use of proton pump inhibitors (PPIs), as well as the editorial on rationalizing the use of PPIs by Ponce and Esplugues (2).…”
Section: Abstract: Proton Pump Inhibitors Prescription Clinical Prmentioning
confidence: 99%
“…Currently, gastroesophageal reflux disease accounts for most of the approved indications for PPIs for long-term use, followed by prophylaxis against nonsteroidal anti-inflammatory drugs (NSAIDs) (1). The high prevalence of gastroesophageal reflux disease, its chronic nature and the concomitant presence of other risk factors such as the aging of the population, which is often associated with increased morbidity or treatments that increase the risk of bleeding such as anticoagulants or antiplatelets, contribute to a very high prescription of PPIs (2,3).…”
Section: Introductionmentioning
confidence: 99%
“…It is necessary that all related works determine economic indicators such as DHD and cost per 100 beds per day that will allow other researchers to make comparisons among different populations and hospitals. Some authors have proposed intervention measures for this problem, with the best results shown by adhesion to clinical practice guidelines and evidence-based protocols (7,37,38).…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, they have been used for different indications from those recommended, as polymedication, with the exception of gastrolesive drugs, which present clearer indications for their prescription, including criteria such as age and risk factors for upper gastrointestinal hemorrhage, and are not simply used as mucosa protectors (5)(6)(7).…”
Section: Introductionmentioning
confidence: 99%